2015
DOI: 10.2355/isijinternational.55.491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot Metal on Decarburization in the EAF and Dissolved Sulfur, Phosphorous, and Nitrogen Content in the Steel

Abstract: The effect of hot metal additions on the decarburization and dissolved sulfur, phosphorous, and nitrogen content in the steel of a DC EAF was investigated. The addition of hot metal of maximum 36% provided heat into the EAF allowing faster melting and reduced power on times of the furnace. The increased melting rate lowered the FeO in the slag and seems to allow faster kinetics for CaO dissolution into the slag. Hot metal utilization into the slag resulted in higher phosphorous distribution ratios compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…Meanwhile, the gibbs free energy change D r G h m; ðS 2À Þ slag and distribution equilibrium constant K gas-slag of the reaction [1] between gas and slag phases can be described as Eqs. [3] and [4]. [13] …”
Section: A Reaction Mechanism Of Desulfurization and Resulfurizationmentioning
confidence: 96%
See 1 more Smart Citation
“…Meanwhile, the gibbs free energy change D r G h m; ðS 2À Þ slag and distribution equilibrium constant K gas-slag of the reaction [1] between gas and slag phases can be described as Eqs. [3] and [4]. [13] …”
Section: A Reaction Mechanism Of Desulfurization and Resulfurizationmentioning
confidence: 96%
“…[3] Thus, after classifying the actual production sulfur distribution ratio based on the same binary basicity, it was linearly fitted to the hot metal temperature and obtained the formulas, as shown in Figure 1 and Table III. Figure 1 shows the effect of hot metal temperature on sulfur distribution at a different binary basicity, which increases with the rise of hot metal temperature from a statistical standpoint, for the rise of temperature is beneficial both to the thermodynamics and kinetics of sulfur distribution reaction.…”
Section: B Influence Rules Of Sulfur Distribution Ratio In Actual Prmentioning
confidence: 99%
“…Accumulation of impurities brings difficulty in steel manufacturing, such as hot shortness during rolling and temper brittleness [7] . The open literature reported that hot metal charging in industrial EAF capacity 50 and 130 ton/h successfully reduced power consumption [6] [8] . Modeling and simulation approaches based on the first principle of mass and energy conservation are effective tools for analyzing the EAF system.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamentals of the BOF converter process have been studied for a long time, and the decarburization has been the topic for many researchers. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The main purpose of the BOF furnace is to decarburize and dephosphorize the hot metal delivered from the blast furnace. 21) As oxygen is blown on the top surface of the metal bath, metal droplets splash into the slag composing mostly of FeO, CaO and SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…solid carbon, 4,10,12,17) or different oxygen partial pressure 14) has been used as reacting substance. Experiments to study the effect of P and S has also been carried out, 7,15,16,20) which is an interesting part of the topic as the demands on steel grades are increasing.…”
Section: Introductionmentioning
confidence: 99%